Effect of Utilitarian Value, Hedonic Value, and Symbolic Value on Purchase Decision in Shopee Live Streaming at Ladyfame Official Shop - Laras, Esti; Aprilani, Deddy; Roni, May (Journal of Business Management and Economic Development, 2025)
The fashion industry in Bandar Lampung continues to grow alongside technological advancements. One strategy to boost sales is the use of live streaming features on marketplaces. Ladyfame, a fashion-focused online shop, utilizes this feature through Shopee Live. This study aims to examine the influence of utilitarian value, hedonic value, and symbolic value on purchase decisions during Shopee Ladyfame Official Shop’s live streaming. This research is explanatory and uses a quantitative approach. The population consists of Ladyfame consumers in Indonesia who have watched and made purchases via Shopee Live. A sample of 96 respondents was selected using purposive sampling and the Cochran formula. Data analysis was conducted using multiple linear regression with SPSS version 29. The results of this study reveal that both partially and simultaneously, utilitarian value, hedonic value, and symbolic value have a positive and significant influence on purchase decisions during Shopee live streaming at Ladyfame Official Shop. Based on these findings, it is recommended that Ladyfame enhance the informative and efficient aspects of product presentation in live streaming sessions, such as through clear product descriptions, detailed demonstrations, and easy purchasing access. For future researchers, it is recommended to expand the research model by including other variables such as trust in influencers, price perception, and visual streaming quality, which may influence purchase decisions.